Citation analysis of social science research: a case study of bachelor degree research project reports of a Nigerian university 2009-2013 (2014)
The study is an analysis of the citations in the research project reports of Social Science Bachelor degree graduates between 2009 and 2013 submitted to the Covenant University Library. This was with a view to determine the type of information resources that were cited more by the researchers, find the average citations made per project report, determine the amount of internet or e-resources cited as against print resources and ascertain the recency of citations and author preference in the ICT age. It was revealed that the authors cited more from textbooks than journal and internet /electronic resources. Citation from books was 69.4% followed by journals 16% and Internet/ E-Resources 8% among others. The average of 39 citations per report generally was discovered. 34.6% of the total citations were Very Recent, 21% citations were Recent, while 13.4% citations were Not Very Recent and 31% of the total citations were Not Recent. The researcher’s author preference is foreign authors as against African authors. It is recommended that the Library must engage more in a variety of education and information literacy skill programmes. Project supervisors should randomly check citations to deter students from using spurious authors. Students should seek for more recent materials and there should be lectures on citation/reference of consulted materials especially internet/e-resources. African authors should intensify writing and publishing among others.